Flexural strength, flexural modulus and microhardness of milled vs. fused deposition modeling printed Zirconia; effect of conventional vs. speed sintering - Maher S. Hajjaj; Rana A. A. Alamoudi; Walaa A. Babeer; Waleed Y. Rizg; Ahmad A. Basalah; Saeed J. Alzahrani; Hanin E. Yeslam (BMC, 2024)
Abstract Background Various methods can be used for creating zirconia dental restorations, including 3-dimensional (3D) printing and computer-aided design/ computer-aided manufacturing (CAD/CAM) milling. The fused deposition modeling (FDM) printing method for zirconia presents numerous advantages, albeit research on the mechanical properties of these materials and resultant restorations remains scarce. Such developments are undeniably intriguing and warrant further investigation. The objective of the present study was to evaluate the impact of the sintering firing cycle (Conventional vs. Speed sintering) on the flexural strength, flexural modulus, and Vickers Microhardness of milled vs. FDM printed zirconia. Methods A total of 60 bars (2 × 5 × 27 mm) were fabricated for flexural strength testing, along with 40 discs (12 × 1.5 mm) for Vickers microhardness testing. Half of the specimens underwent conventional sintering, while the other half underwent a speed sintering cycle. The flexural strength and modulus were determined by a three-point bending test in a universal testing machine. The microhardness of the specimens was evaluated using a Vickers microhardness tester. Statistical analysis was performed using a two-way ANOVA test with a post-hoc Tukey test (p < 0.05). Results CAD/CAM milled zirconia had significantly higher flexural strength and modulus than FDM-printed zirconia. The sintering process did not significantly affect the flexural strength or modulus of milled or FDM-printed zirconia. The milled speed sintering group had significantly higher values in the Vickers microhardness test compared to the other groups. Conclusions The mechanical properties of FDM-printed zirconia specimens were not found to be comparable to those of milled zirconia. Speed sintering cycle may produce milled zirconia restorations with similar flexural strength and modulus to conventional sintering, and even higher Vickers Microhardness values.